Chaotic experiences and low-income children's social-emotional development. (November 2016) - Bobbitt, Kaeley C.; Gershoff, Elizabeth T.
Abstract: Development in early childhood is increasingly likely to take place in multiple contexts. Continuity and discontinuity in children's experiences across multiple contexts have important implications for their development. This study examines the extent to which children experience chaos in their homes and in their preschool settings is linked with their social-emotional development over the course of the preschool year. Data from a large, representative sample of low-income preschool children attending Head Start was used to test a series of multi-level models. Children whose experiences of their homes were highly chaotic, regardless of the how chaotic their experiences of their classroom were, decreased in their social-emotional skills over the preschool year. Chaotic experiences in the home environment thus appear to have more influence on children's development than do chaotic preschool experiences. Highlights: Home and classroom chaos predict change in children's social-emotional development. The home environment is the predominant influence on social-emotional growth. Children from non-chaotic homes gained most over the preschool year. Early education settings must incorporate children's home and family experiences.